Application of Cultural Based Discovery Method to Increase The Mathematical Solution Ability of Academic Year Students 2019/2020 - Dwi Novita Sari; Nurul Azmi (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2020)
The development of science at the present time requires educators to create learning innovations especially mathematics learning that is associated with cultural values. In line with the goals of the State who want to advance the national culture of Indonesia in the midst of world civilization by ensuring the freedom of the people in maintaining and developing their cultural values. With the hope of collaborating between learning with local culture, in addition to preserving the existing culture, it can also help students understand the material. Educators are also required to be able to use various methods in learning so that the learning atmosphere feels comfortable. The more methods and exercises used, the higher the level of mathematical problem solving possessed and conversely the less variety of methods and exercises used, the lower the level of mathematical problem solving of students. The purpose of this study is to improve students' mathematical problem solving abilities by applying a culture-based guided discovery method. This research uses the Classroom Action Research (CAR) method. The research instrument used was a mathematical problem-solving ability test. Output targets to be achieved in this study are journals.